The course of gout in a patient with Cushing’s disease after successful surgical treatment - L. K. Dzeranova; M. S. Eliseev; O. O. Golounina; E. V. Cheremushkina; E. A. Pigarova; G. A. Melnichenko (Ожирение и метаболизм, 2023)
Endogenous  hypercortisolism  is a severe endocrine  disease characterized by prolonged  exposure to excessive amounts of glucocorticoid hormones, accompanied by a wide range of symptoms and complications, including immunosuppression. Timely surgical treatment in most cases allows to save the patient’s life, significantly improve its quality. However, restoration of the normal concentration of glucocorticoid  hormones can become a trigger factor in the development or exacerbation of autoimmune and auto-inflammatory diseases. We present a clinical case of atypical gout in a patient with hypercortisolism and a progressive increase in symptoms of the disease after successful surgical treatment for Cushing’s disease and achieving stable remission. The issues of diagnosis and treatment of this group of autoinflammatory diseases are highlighted, the leading clinical and radiological  symptoms are considered, the differential diagnosis  of microcrystalline (metabolic) arthritis is presented. Despite the widespread, the diagnosis and treatment of this group of diseases still cause difficulties for specialists. A competent choice of drug therapy allows to fully control diseases considered in the article, including when they are combined, and thereby improve the quality of life of the patient.